"In-house" preparation of 99mTc-EDDA/HYNIC-TOC, a specific targeting agent for somatostatin receptor scintigraphy - Sonja Kuzmanovska; Olivija Vaskova; Marina Zdraveska Kocovska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
The use of radiolabeled peptide ligands as diagnostics and therapeutics in nuclear oncology has increased recently. One of the most frequently used radiopharmaceutical is 99mTc-EDDA/HYNIC-TOC, a somatostatin analog with affinity for certain types of somatostatin receptors, overexpressed in tumors of neuroendocrine origin. The radiopharmaceutical is not readily available; therefore we introduced its "in house" preparation within project activities supported by the International Atomic Energy Agency (IAEA). We optimized the radiolabeling protocol, prepared a small batch of frozen kits, performed ITLC quality control and animal biodistribution during the preclinical evaluation procedures. The co-ligand exchange labeling procedure was carried out at 100°C during 10 min, resulting in radiochemical purity >90%. The biodistribution scintigrams in normal Wistar rats showed rapid blood clearance after 15 min and predominant kidney accumulation after 4 h, in accordance with the data reported by other authors. Storage stability of the formulated small batch frozen kit (-20°C) was evaluated within 6 months, with radiolabeling yield ranging between 94,3% and 96,9%. We conclude that frozen kit can be a safe alternative to the freeze-dried for small batch in house production, and after the satisfactory preclinical evaluation, the "in house" prepared 99mTc-EDDA/ HYNIC-TOC can be introduced in clinical practice as specific targeting agent for somatostatin receptor scintigraphy.